أثر مخلفات بلاط السيراميك على ديمومة الخرسانة المسلحة بالألياف الزجاجية GRC - علي خيربك; عماد فاضل; سوزان تفاحة (Tishreen University, 2018)
With the aim to improve the durability of GRC and in the context of sustainability applications and reduce the consumption of cement and the recycling of demolition waste, which is estimated in millions of tons in Syria due to the war in it. This study was done to test the role of ceramic powder as supplementary cementing material by 10% -15% -20% - 25% in GRC mixture. And determination of the effect of it on the consistency and flexure strength over 180 days, and tested its role in improving the micro-structure of the mixture by reducing the content of the Ca(OH)2 which tested using X-Ray Diffraction (XRD) and Energy Dispersive X-Ray (EDX) techniques, which reduced the erosion of fibers as shown in images by Scanning Electronic Electron Microscopy (SEM). As well as studied the role of ceramic in controlling the degradation of the material over time experienced by immersion in hot water 50 ͦ for 150 days and by drying - wetting cycles, also been studying the effect of ceramic powder on  absorption and porosity and Resistance of sulfates attacks. The results showed that ceramic powder has no negative effect on consistency or mechanical properties and improved all the studied durability factors. بهدف تحسين ديمومة مادة GRC وضمن سياق تطبيقات الاستدامة والتقليل من استهلاك الاسمنت وإعادة تدوير مخلفات الهدم التي أصبحت تقدر بملايين الأطنان في سورية نتيجة الحرب الدائرة فيها. تم القيام بهذه الدراسة لاختبار دور مطحون السيراميك كمستبدل اسمنتي بنسب 10%- 15%- 20%- 25% بخلطات GRC، وتحديد تأثير كل منها على قوام الخلطة ومقاومة الشد بالانعطاف على مدى 180 يوم، وكذلك اختبر دورها في تحسين البنية الداخلية للخلطة من خلال التقليل من محتوى البورتلانديت Ca(OH)2 وزيادة C-S-H & C-A-S-H gel فيها والذي اختبر باستخدام تقنيةX-Ray Diffraction (XRD) وتقنية Energy Dispersive X-Ray (EDX) الأمر الذي قلل بدوره من تهتك الألياف كما أظهرت الصور بالمجهر الالكتروني Scanning Electron Microscopy (SEM) وكذلك درس دور مطحون السيراميك في السيطرة على التدهور الحاصل للمادة بمرور الزمن والذي اختبر من خلال الغمر بالماء الساخن بدرجة 50 ͦ مدة 150 يوم وبحلقات التجفيف - ترطيب، وتم أيضاً دراسة أثر مطحون السيراميك على الامتصاص والمسامية ومقاومة هجمات الكبريتات. أظهرت النتائج أنه ليس لمطحون السيراميك أثر سلبي يذكر على قوام الخلطة أو على الخصائص الميكانيكية وتحسنت جميع عوامل الديمومة المدروسة.